Equation is <span>-4x+6y-5z=60
x-intercept is obtained by assuming y=0, z=0, and solving for x.
-4x+0-0=60 => x=-15, hence x-intercept is (-15,0,0)
Similarly for y-intercept, assume x=0,z=0 =>
0+6y-0=60 => y=60/6=10 => y-intercept is (0,10,0)
Again, for the z-intercept, assume x=0,y=0 =>
0+0-5z=60 => z=-12 => z-intercept is (0,0,-12)</span>
Answer:
106
Step-by-step explanation:
divided 320 by 3
Answer:the price now is $128
Step-by-step explanation:
you can get this by dividing the cost by the percentage it has risen by. For example: 120 / 15 = 8 and then you add 8 to the initial price
Answer:
-4(-41)
Step-by-step explanation:
Answer: The area of the new parallelogram is multiplied by 18
Step-by-step explanation: Let the base and the height of the original parallelogram be ' x '
Base of the parallelogram = x
Height of the parallelogram = x
Area of parallelogram = l × b = lb
= x × x = x²
∴ Area of the original parallelogram = x²
∴ The base is multiplied by 3 = 3x
The height is multiplied by 6 = 6x
∴ Area of new parallelogram = 3x × 6x = 18x²
∴ The area of the new parallelogram is multiplied by = 18x²/ x²
= 18
<u><em>Please mark this as brainliest</em></u>